Syntheses, Crystal Structures and Physical Properties of Chromium and Rhodium Hydrogarnets Ca3[Cr(OH)6]2, Sr3[Cr(OH)6]2 and Sr3[Rh(OH)6]2. Issue 10 (4th March 2019) - Albrecht, Ralf; Hunger, Jens; Doert, Thomas; Ruck, Michael
Abstract : The hydrogarnets Ca3 [Cr(OH)6 ]2, Sr3 [Cr(OH)6 ]2 and Sr3 [Rh(OH)6 ]2 were synthesized under hydroflux condition at about 200 °C. The starting materials Ca(NO3 )2 · 6H2 O, Sr(NO3 )2, Cr(NO3 )3 · 9H2 O and RhI3 were reacted in mixtures of water and potassium hydroxide with molar ratios between 1.2:1 and 3:1. The structures and thermal properties of these hydrogarnets were studied by X‐ray diffraction, thermal analysis, electron microscopy as well as infrared and UV/Vis spectroscopy. Low temperature single‐crystal diffraction measurements revealed katoite‐like structures, in which the tetrahedrally coordinated metal positions of the garnet are unoccupied and hydroxide ions replace the oxide anions for charge compensation. IR spectroscopy confirmed the presence of hydroxide groups, which form weak hydrogen bonds. The thermal decomposition of Ca3 [Cr III (OH)6 ]2 first yields CaCr VI O4 and CaO at 314 °C, which then react to Ca3 (Cr V O4 )2 at 823 °C. The decomposition of Sr3 [Cr(OH)6 ]2 proceeds similarly in the first step but results in the mixed valent compound Sr2.67 (Cr V O4 )1.33 (Cr VI O4 )0.67 at 730 °C. The decomposition of Sr3 [Rh(OH)6 ]2 under the same conditions results in Sr10.5 Rh III 3 Rh IV 4.5 O24 . Abstract : The katoite‐like hydrogarnets Ca3 [Cr(OH)6 ]2, Sr3 [Cr(OH)6 ]2 and Sr3 [Rh(OH)6 ]2 were synthesized under hydroflux conditions. Their thermal decompositions can be used to form complex transition metal oxides at notably lower temperatures than previously reported.